Efficient IT project management system: features and classification - Novosad, Yurii (Вежа-Друк, 2023)
In recent years, the IT sector has significantly expanded its boundaries and has become a key player in the external economic activities of many countries. Ukraine is no exception, where the IT industry is rapidly developing and making a significant contribution to the GDP. IT projects have become essential for implementing business projects of various scales, serving as the foundation for creating new products, high-tech manufacturing, and information systems. Ukraine holds leading positions in the field of IT development and services. Ukrainian IT companies provide their services in various countries around the world, including the United States and the United Kingdom. This demonstrates the high quality of work, professionalism, and competitiveness of Ukrainian IT companies.
Keywords: IT sector; IT projects; project management; effective management system; 005.8:004.4